Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0173752
|View full text |Cite
|
Sign up to set email alerts
|

Toward a phenological mismatch in estuarine pelagic food web?

Abstract: Alterations of species phenology in response to climate change are now unquestionable. Until now, most studies have reported precocious occurrence of life cycle events as a major phenological response. Desynchronizations of biotic interactions, in particular predator-prey relationships, are however assumed to strongly impact ecosystems’ functioning, as formalized by the Match-Mismatch Hypothesis (MMH). Temporal synchronicity between juvenile fish and zooplankton in estuaries is therefore of essential interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 75 publications
2
17
0
Order By: Relevance
“…Warmer winters brought on by global climate change (IPCC , ) may therefore shift species’ reproductive cycles to begin earlier, or eliminate seasonality altogether, resulting in poorly provisioned or ill‐timed larvae (Chevillot et al. ). Such impacts were clearly demonstrated using a long‐term dataset (1973–2001) of estuarine clam Macoma balthica reproduction and temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warmer winters brought on by global climate change (IPCC , ) may therefore shift species’ reproductive cycles to begin earlier, or eliminate seasonality altogether, resulting in poorly provisioned or ill‐timed larvae (Chevillot et al. ). Such impacts were clearly demonstrated using a long‐term dataset (1973–2001) of estuarine clam Macoma balthica reproduction and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some temperate bivalve species have a thermal threshold for gametogenesis and enter a period of reproductive inactivity, or "quiescence," which is believed necessary for successive spawning (Hopkins 1937, Loosanoff 1942, Giese 1959. Warmer winters brought on by global climate change (IPCC 2013(IPCC , 2019 may therefore shift species' reproductive cycles to begin earlier, or eliminate seasonality altogether, resulting in poorly provisioned or ill-timed larvae (Chevillot et al 2017). Such impacts were clearly demonstrated using a long-term dataset of estuarine clam Macoma balthica reproduction and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Among these components of global change, the best documented is global warming, which is due to increased greenhouse gas emission by human activities (IPCC, ), affecting the biosphere at all scales (Gattuso et al., ). Global warming already has visible impacts on the ecology of living organisms (Hughes, ; Walther et al., ) with impacts on their phenology (Chevillot et al., ; Menzel et al., ) and modification of distribution areas (Cheung et al., ; Lassalle, Crouzet, & Rochard, ; Nicolas et al., ; Rougier et al., ). Global warming alters biogeochemical cycles such as the water cycle.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been developed for salmon in the context of climate change with the notion of thermal refuge (Frechette, Dugdale, Dodson, & Bergeron, 2018). However, the cause of the decline needs to be explored for other habitat components and life stages, such as low levels of dissolved oxygen for juveniles in estuaries (Chevillot et al, 2017;Ficklin, Stewart, & Maurer, 2013;Portner & Knust, 2007). The identification of these potential spawning grounds will require databases of environmental factors and hydroclimatic models in French rivers at high resolutions.…”
Section: Management Implicationsmentioning
confidence: 99%
“…For example, if anadromous fishes, such as salmon, base their spawning behaviour on factors that are unaffected by global warming, such as photoperiod Quinn & Adams, 1996), the conditions triggering spawning may become desynchronised from the conditions that determine the optimal time for reproduction, and spawners may reproduce in suboptimal conditions. The spawning period may not match the peak of prey for juveniles (Chevillot et al, 2017) and could ultimately affect offspring survival, as observed in migratory birds (Visser, Noordwijk, Tinbergen, & Lessells, 1998).…”
Section: Introductionmentioning
confidence: 99%